Association of smoking with the survival of patients with brain metastasis of lung cancer - Yu, Jiayi; Zhang, Yu; Liu, Zheran; He, Yan; Pei, Yiyan; Zhang, Renjie; Peng, Xingchen; Fang, Fang (Frontiers in Neurology, 2023)
Background Smoking is associated with increased mortality in patients with cancer. However, there are limited data on the impact of smoking on the survival of patients with brain metastases. Therefore, this study aimed to evaluate whether smoking was associated with survival and whether smoking cessation was beneficial to these patients. Methods This study used lung cancer with a brain metastasis cohort of the West China Hospital of Sichuan University from 2013 to 2021. Patients were stratified according to smoking history; the distribution, clinical characteristics, and survival data of each group were estimated. Kaplan-Meier analysis and risk analysis were performed for the survival endpoint. Results Of the 2,647 patients included in the analysis, the median age was 57.8 years, and 55.4% were men. Among them, 67.1% had no smoking history, 18.9% still smoked, and 14% reported quitting smoking. Compared with never smokers, current smokers [HR, 1.51 (95% CI, 1.35-1.69), p < 0.01] and former smokers [HR, 1.32 (95% CI, 1.16-1.49), p<0.01] had an increased risk of death. However, quitting smoking was not associated with improved survival [HR, 0.90 (95% CI, 0.77-1.04), p = 0.16]. The overall survival increased with the increase of smoking cessation years. Conclusions In lung cancer patients with brain metastases, smoking was associated with an increased risk of death, but quitting smoking was not associated with improved survival.